Alleilic difference in the putative gene ipk1 sequence and phytic acid (INSP6) content in Black Pepper - Gladish Mary Joy (Department of Plant Breeding & Genetics, College of Agriculture, 2019)
Black pepper (Piper nigrum L.) is one of the world’s highly demanded and most traded spices with high medicinal and therapeutic values. A unigene pnc135 (995 bp) was developed by the Expressed sequence tags data obtained by next generation sequencing. This unigene was found to show similarity with ipk1 gene reported in other crop species which encodes for inositol pentakisphosphate-2 kinase enzyme (Unpublished data, Sujatha,R.). This enzyme is involved in the phosphorylation of inositol pentakisphosphate to inositol hexakisphosphate or phytic acid (InsP6), last step in the biosynthetic pathway of phytic acid. This unigene was later partially sequenced (1072 bp) towards the 3’ end by directional genome walking by Giridhari (2017). Phytic acid functions as the major storage form of phosphorus in seeds, cereals and legumes possessing significant benefits including signalling, plant communication, messenger RNA transport etc. However, phytic acid also acts as an anti-nutrient in animals as its chelating property will cause malnutrition in organisms and also leads to environmental pollution due to phosphorus excretion by non-ruminant animals. Therefore researchers are finding ways to create ipk1 mutants for either to decrease or increase the phytic acid content in organisms. However the genetic information about the black pepper crop remains very limited and the metabolic pathways and the genes related to it are also poorly understood. So in this study entitled “Allelic difference in the putative gene ipk1 sequence and phytic acid (InsP6) content in black pepper (Piper nigrum L.)”, the objective was to find out the flanking region towards the 5’ region of pnipk1 gene fragment (1072 bp) reported earlier by Giridhari (2017), to identify the allelic differences in pnipk1 gene in 10 black pepper genotypes and to estimate and quantify the phytic acid content in these 10 black pepper genotypes using polyacrylamide gel electrophoresis (PAGE). Genomic DNA was isolated from Panniyur 1 variety of black pepper and used it for the whole genome amplification by Rolling Circle Amplification method using Phi 29 DNA polymerase and walker adaptors (WA1, WA2, WA3 and WA4) reported by Reddy et al. (2008). After whole genome amplification, genome walking using primer combinations of walker primers, locus specific primers and nested locus specific primers were performed to find out the flanking region towards the 5’ region of pnipk1(1072 bp) gene fragment of black pepper. The walker primers (WP1 and WP2) used for genome walking were same as that of reported in Reddy et al. (2008) and the locus and nested locus specific primers were designed on the basis of pnipk1 gene fragment (1072 bp) sequenced by Giridhari (2017). From the nested PCR amplification four products, two amplicons, A1R3 and A4R3, each at two different temperatures viz., 51.6⁰Ϲ and 56.8⁰Ϲ were obtained and sequenced. On assembling the sequences a contig of length 523 bp was obtained towards the 5’ region of pnipk1 gene fragment and this showed similarity to ipk1 gene in other crops. This 523 bp contig was assembled with ipk1 gene fragment (pnipk1-1072 bp) to get a total length of 1535 bp. The newly assembled ipk1 gene sequence (pnipk1-1535 bp) was analysed in ORF finder for the coding region and found an Open Reading Frame (ORF) with 645 bp encoding for 214 amino acids. Phylogenetic analysis of the sequence and translated amino acid sequence showed closer evolutionary relationship with that of Dendrobium catenatum. Primers were designed based upon the pnipk1 gene sequence (1535 bp) to amplify the genomic DNA of Panniyur 1 and other 10 black pepper genotypes. The selected 10 genotypes were Panniyur 5, Panniyur 7, Chettanvally, Kottanadan, Karimunda 7, Thottamundy, Karimunda kuttyatur, Payyanganam 2, PRS 160 and Chumala. Amplification of pnipk1 gene (1535 bp) was obtained from genomic DNA of Panniyur 1, Panniyur 5, Panniyur 7 and Karimunda 7 with the expected of amplicon size indicating a similar sequence among these genotypes. Whereas amplification was not obtained in genomic DNA in rest of the genotypes showing allelic variation is present for ipk1 gene in these genotypes. To estimate and quantify the phytic acid content in Panniyur 1 and 10 black pepper genotypes, polyacrylamide gel electrophoresis (PAGE) was performed. Phytic acid was extracted from black pepper varieties same as that of selected for allelic difference analysis in ipk1 gene (pnipk1-1535 bp). The samples were loaded with phytate standards and band intensities of each concentration were determined with Gelquant.NET. The values of phytic acid in black pepper genotypes were estimated by the standard curve. The quantity of phytic acid in samples are: Panniyur 5 with 502.5nmoles/g, Panniyur 7 with 367.5nmoles/g, Chettanvally-511.5nmoles/g, Kottanadan-463.5nmoles/g, Karimunda7- 387nmoles/g, Chumala-201nmoles/g, Karimunda kuttyatur-637.5nmoles/g, Payyanganam 2-196.5nmoles/g and Panniyur 1- 275 nmoles/g, Thotamundy- 198nmoles/g, PRS 160-697.5nmoles/g. Based on the phytic acid content in the black pepper genotypes, they can be classified into low (<210 nmoles/g), medium (210-510 nmoles/g) and high (>510 nmoles/g) phytic acid content. The ipk1 gene fragment (pnipk1-1535 bp) was amplified in the genotypes Panniyur 1, Panniyur 5, Panniyur 7 and Karimunda 7. These genotypes all came under the category of medium phytic acid content group. The study resulted in sequencing a total of 1535 bp long segment of ipk1 gene black pepper variety Panniyur 1 and analysing the presence of allelic variation in ipk1 gene and phytic acid content in selected black pepper genotypes.